Gatifloxacin Bipolymeric Ophthalmic Inserts:in vitroStudies on Drug Release - SOUNDRAPANDIAN, C.; SENTHIL KUMAR, B.; KRISHNAMOORTHY, B.; DAMODHARAN, N. (Asian Journal of Chemistry, 2010)
A variety of conventional ophthalmic drug delivery options exist. However, once a day options are highly in need due to obvious reasons. Bipolymeric ophthalmic inserts of gelatin and alginate, cross-linked with Ca2+, with gatifloxacin loaded in different concentrations, were obtained by a casting-solvent evaporation method. The inserts were characterized for their mechanical properties, as well as the studies of the factors that influence the drug releasing from these ophthalmic inserts. These factors included the component ratio of polymers, the loaded amount of gatifloxacin, the thickness of the drug loaded ophthalmic inserts and the cross-linking time with Ca2+ and others. The best values of the tensile strength and breaking elongation of bipolymeric ophthalmic inserts were obtained when the gelatin content was 50 % w/v. The results of in vitro drug release studies showed that the amount of gatifloxacin released decreased with an increase in the proportion of gelatin present in the inserts. Moreover, the release rate of drug decreased as the amount of drug load in the inserts increased. It was also observed that as the thickness of the inserts increased drug release decreased. When the cross-linking time of these ophthalmic inserts in the Ca2+ solution increased, the drug release rate decreased. All the results indicated that the gelatin-alginate bipolymeric inserts suitability in releasing gatifloxacin and to act potentially as a drug delivery system.